The Hypocrisy Behind The Absolute Banning Of Torture: Historical Fallacies, Factual Necessities, And Judicial Artifices - Morsy, Abdelalim (AUC Knowledge Fountain, 2025)
The absolute and non-derogatory prohibition of torture is embedded in almost every international or regional human rights instrument that deals with civil rights. However, this ban witnesses a diversion between theory and practice. While this diversion is comprehendible in authoritarian states, democratic regimes also implement it in some instances. This usage notably arose in the wake of the 11th of September 2001 and the accompanying usage of physical coercion in the interrogation processes. Simultaneously, some scattered, though notable, scholarly voices started challenging the absolute prohibition against torture. This pro-torture school of thought echoed in some legislative and executive works. The judiciary, as well, was in a complicated situation between preserving its heritage in defending human rights and its role in preserving state security. Such a hardship was reflected in the language of the verdicts. The sum of these scholarly, legislative, executive, and judicial momentum was still minor and could not change the well- established absolute prohibition. This paper argues that the denial of absolute prohibition has existed forever and will continue to exist. The 9/11 incidents only brought it to the surface. I further dispute the effectiveness of the focus on absolute prohibition as an effective tool to curb torture with all the hard cases it raises.